HOW TO DO RESEARCH IN INTERNATIONAL RELATIONS ‘CONSTRUCTIVELY’: ANALYSIS OF THE MAIN PHILOSOPHICAL ASSUMPTIONS AND THEORETICAL PRINCIPLES - Jakniūnaitė, Dovilė; Nekrašas, Evaldas (Politologija, 2015)
One of the biggest critiques for the constructivism in international relations discipline is the accusations of abstractiveness and having little substantive to say when talking about world politics. The article asserts that constructivism is not the typical theory of international relations or foreign policy analysis. Constructivism in the discipline is what every constructivist researcher makes of it, using a few fundamental statements about the analysis of social reality. In order to show how the constructivist international relations researchers apply the fundamental principles of the constructivist analysis of social reality to form their models of analysis, firstly, the article explains the metatheoretical assumptions of constructivism and the main problems that emerge trying to apply them in empirical research. The word constructivism is used on many different levels of thought, so the classification provided by Jorgensen is used. He talks about philosophical, metetheoretical, theoretical and empirical constructivisms. Using Ze’ev’s categorization of philosophical positions on epistemological and ontological questions, it was shown that mostly constructivist researchers tend to go under the label of constructivist idealism, according to which the actor has both the epistemological and ontological influence on the world. Metatheoretical constructivism is best represented by Berger and Luckmann’s book The Social Construction of Reality and its main thesis that the society is the constant process of externalisation, objectivisation and internalisation. Secondly, through three fundamental statements of metatheoretical constructivism (on intersubjective construction of meanings, relationship of ideas and materiality, and mutual constitutive relation of structure and agency) it is demonstrated how they are transformed and applied in more particular theoretical and empirical works of international relation discipline. The analysis of social construction of meaning is presented through the research on the representations of US national interests during the Cold war. The securitization theory demonstrates how the analysis of the formulation of the security problems allows combining the ideal and the material factors of the state agency into one theoretical model. The mutuality of structure and agency is demonstrated through the international norm research. In the end several recommendation are provided on the main principles of constructivist research in international relations. It is recommended, first, not to be afraid of methodological and theoretical experiments, second, to realize that the constructivist methodological positions is best defined as methodological pluralism, third, to remember that the constructivist research design is inseparable from the researched problem and the understanding of the social world.